Population-Based Study of Pertussis Incidence and Risk Factors among Persons >50 Years of Age, Australia - Rodney Pearce; Jing Chen; Ken L. Chin; Adrienne Guignard; Leah-Anne Latorre; C. Raina MacIntyre; Brittany Schoeninger; Sumitra Shantakumar (Emerging Infectious Diseases, 2024)
Despite vaccination programs, pertussis has been poorly controlled, especially among older adults in Australia. This longitudinal, retrospective, observational study aimed to estimate the incidence and risk factors of pertussis among persons ≥50 years of age in Australia in the primary care setting, including those with underlying chronic obstructive pulmonary disease (COPD) or asthma. We used the IQVIA general practitioner electronic medical record database to identify patients ≥50 years of age with a clinical diagnosis of pertussis during 2015–2019. Pertussis incidence rates ranged from 57.6 to 91.4 per 100,000 persons and were higher among women and highest in those 50–64 years of age. Patients with COPD or asthma had higher incidence rates and an increased risk for pertussis compared with the overall population ≥50 years of age. Our findings suggest that persons ≥50 years of age in Australia with COPD or asthma have a higher incidence of and risk for pertussis diagnosis.